Researches of the Internal Mechanical Stresses Arising in Si-SiO2-PZT Structures - D.A. Kovalenko; V.V. Petrov (Журнал нано- та електронної фізики)
The investigations directed on identification of growth mechanisms of ferroelectric thin films of lead zirconate titanate (PZT) on the oxidized silicon substrates are described in the work. It is shown that the growth rate of a ferroelectric film is equal to about 15-18 nm/min, and films are formed by the Stransky-Krastanov mechanism. Results of the theoretical study of the internal mechanical stresses arising because of the difference in the coefficients of thermal expansion of materials of a silicon substrate, oxidized silicon underlayer and a PZT film are given. Results of the pilot studies of internal mechanical stresses which coincide with the calculated results in the thickness range of PZT films of 100-300 nm are presented.